Testing the Howard-Sheth Model in University Marketing - Ion-Danut LIXANDRU (Communications of International Proceedings, 2021)
As a basic principle for understanding and predicting the operation of a system, the modeling process is, without a doubt, a technique that helps to develop any phenomenon. A concept almost never used in university marketing is marketing modeling. The need for this process stems from the need to know exactly certain phenomena that occur around the marketing activity of any organization. It is easy to understand that the modeling process is closely related to making good decisions, creating effective strategies. The aim of this paper is to observe the degree of applicability of the Howard-Sheth behavior model in the process of attracting students in the purchase of university products (bachelor's / master's / doctoral program). The paper presents an analysis of the most important behavioral influencing factors that act on the acquisition decision. From their analysis, a decision tree emerged that demonstrates the applicability of the model, model subjected to a sensitivity analysis and then correlated the most important influencing factors to observe the difference between respondents. At the same time, in accordance with the results, it was decided to add a new element in the analyzed model.
Keywords: marketing; university marketing; marketing models; consumer behavior